Domestic and Family Violence: Responses and Approaches across the Australian Churches - Pepper, Miriam (Religions, 2022)
Domestic and family violence (DFV) is a serious and widespread problem in Australia and across the world, including in faith communities. There are calls for research to assist churches to better recognize, respond to and prevent violence. This study draws on data from the 2016 Australian National Church Life Survey (n = 883 senior local church leaders, n = 1270 churchgoers) to provide the first Australia-wide cross-denominational statistics on Christian clergy responses to DFV. Two-thirds of leaders had previously dealt with DFV situations in their ministry, primarily responding to victims of abuse by referring them to specialist support services and by counselling them. The findings suggest a particular depth of experience with DFV situations and strength of awareness of the needs of victims for safety and specialist support among Salvationist leaders. While, overall, a substantial majority of churchgoers felt that they could approach their church for help if they were experiencing DFV, just half of Catholics felt that they could do so. Future research should explore responses to DFV in specific denominations and culturally and linguistic diverse contexts in more detail and seek to understand the practices used by the large minority of clergy who are dealing with perpetrators.